Mapping and the Citizen Sensor 2017
DOI: 10.5334/bbf.b
|View full text |Cite
|
Sign up to set email alerts
|

Sources of VGI for Mapping

Abstract: The concept of Volunteered Geographic Information (VGI) is often exemplified by the mapping of features in OpenStreetMap (OSM), yet there are many other sources of VGI available. Some VGI is very focused on the creation of map-based products, while in other applications location is simply one attribute that is routinely collected, due to the proliferation of Global Positioning System (GPS) enabled devices, e.g. mobile phones and tablets. This chapter aims to provide an overview of the variety of sources of VGI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 62 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…In Chapter 4, Touya et al (2017) address the challenges of automated mapmaking using VGI as the input data, and the authors consider OSM as a key source, but not the only source, of this VGI data. Chapter 2, See et al (2017) has already indicated that there are many sources of VGI available today. While OSM is open data and is licensed under the Open Data Commons Open Database License (ODbL), there are privacy and ethical issues around the reuse of OSM data.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Chapter 4, Touya et al (2017) address the challenges of automated mapmaking using VGI as the input data, and the authors consider OSM as a key source, but not the only source, of this VGI data. Chapter 2, See et al (2017) has already indicated that there are many sources of VGI available today. While OSM is open data and is licensed under the Open Data Commons Open Database License (ODbL), there are privacy and ethical issues around the reuse of OSM data.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…While OSM is only one of many well established and well known VGI projects (See et al, 2016), it holds a dominant position in the VGI landscape. Chapter 2 of this book, by See et al (2017), gives an overview of different sources of VGI in the context of its usage and characteristics. In recent years OSM has attracted very significant research attention (Mooney, 2015) and could almost be considered a field of research in its own right (Jokar Arsanjani et al, 2015); given the influence of OSM on the VGI and citizen sensor research landscape, this chapter will provide an introduction to and overview of the OSM project.…”
Section: Introductionmentioning
confidence: 99%
“…VGI is still a relatively new field of research; subsequently there is not a great deal of published knowledge or guidelines available on these issues in VGI. Although VGI tends to be associated with the collection and supply of explicitly geographic material, such as OSM (see Chapters 3 and 4 - Mooney and Minghini, 2017;Touya et al, 2017) or citizen science projects (see Chapters 1 and 2 - Foody et al, 2017;See et al, 2017), it is certainly not limited to this type of materials. As means of a short motivating example, we consider geotagged photographs.…”
Section: The Role Of the Citizen Within Privacy Legal And Ethical Ismentioning
confidence: 99%
“…The nature of VGI datasets -see Chapter 2 by See et al (2017) and Chapter 3 by Mooney and Minghini (2017) -and their quality aspects play an important role in the choices regarding visualisation. Past research (Buttenfield and Beard, 1994;Buttenfield and Weibel, 1988;MacEachren, 1992;MacEachren, 1995) has proved that the selection of a visualisation method should be related to the quality element represented and the measure/indicator used.…”
Section: Vgi Data Qualitymentioning
confidence: 99%